1986
DOI: 10.1111/j.1365-246x.1986.tb01085.x
|View full text |Cite
|
Sign up to set email alerts
|

Fundamentals of Geophysical Data Processing, 2nd edn

Abstract: Book reviews 217 of the chapters discuss different aspects of this problem. D. Moos presents an interesting case study of VSP in fractured crystalline rock. The importance of both scattering and anelasticity is emphasized. M. Simaan and P. L. Love discuss the synthesis of VSP including the effects of absorption, dispersion and frequency-dependent reflection coefficients. E. Strick in a significant chapter occupying almost a third of the book provides a thorough review of anelasticity and P-wave distortion. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
355
0
8

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 280 publications
(363 citation statements)
references
References 0 publications
0
355
0
8
Order By: Relevance
“…With improvements in data quantity and quality, improved waveform simulation using algorithms based on physically-motivated approximations that describe the frequency-dependent effects of wave propagation are becoming increasingly important [75; 76]. For instance, in the pioneering study of [77], the acoustic parabolic equation of [78] was adapted to study the P-wave traveltime and amplitude anomalies over the NORSAR array. Their results indicated that the 3D heterogeneities in the underlying lithosphere/asthenosphere could be modeled, that the observed large scale traveltime and amplitude anomalies across the array share the same structural origin, and that the teleseismic P-waves are deflected no more than 5 • from the propagation path.…”
Section: Numerical Examplesmentioning
confidence: 99%
“…With improvements in data quantity and quality, improved waveform simulation using algorithms based on physically-motivated approximations that describe the frequency-dependent effects of wave propagation are becoming increasingly important [75; 76]. For instance, in the pioneering study of [77], the acoustic parabolic equation of [78] was adapted to study the P-wave traveltime and amplitude anomalies over the NORSAR array. Their results indicated that the 3D heterogeneities in the underlying lithosphere/asthenosphere could be modeled, that the observed large scale traveltime and amplitude anomalies across the array share the same structural origin, and that the teleseismic P-waves are deflected no more than 5 • from the propagation path.…”
Section: Numerical Examplesmentioning
confidence: 99%
“…A classical way of obtaining the minimum-phase filter, H min , is by using the root method of spectral factorization, where we first find roots in the polynomial given in (3), and reflect the roots located outside the unit circle, into the circle, [1], [3]. Based on the roots inside and on the unit circle, a new polynomial can be computed in the z-domain, which represents the minimum-phase filter.…”
Section: System Modelmentioning
confidence: 99%
“…Wide-angle parabolic approximations are also available. These are frequently used in underwater acoustics and geophysical applications, and lead to higher-order partial differential equations Claerbout (1976). They do not, however, appear that frequently in ultrasonic imaging, where the 15°a pproximation is thought to be adequate.…”
Section: Introductionmentioning
confidence: 99%